Atomistic study on mechanical properties of Al matrix composite with different combining forms of reinforcements - Yongchao Zhu; Na Li; Lijuan Sun; Baolin Wang; Yanlong Gao; Songtao Li (PLoS ONE, 2025)
Models of matrix composite (MMC) are built through molecular dynamic (MD) simulation to study the effect of different combining forms of reinforcements. Diamond particle and graphene nanoplate (GNP) are selected as the two kinds of reinforcements, forming six combinations by changing the location and orientation of them. Then, the same sintering processes are conducted to achieve sintered composites. Bulk volume and Al volume of sintered composite reveal that a compacter structure can be produced in the model with two GNPs those are not parallel, or in the model where the diamond particle is out of the GNP plane. Structural analysis indicates that the ratio of arranged atoms rather than nanopore has a greater impact on Al volume. Tensile results show that the model reinforced by both GNP and diamond in a same plane gives the best performance in both strength and ductility, regardless of its low ratio of arranged atoms that may lead to a further improvement at the larger scale. In other words, GNP can play its role very well along the GNP plane, and diamond particle can improve the property vertical to GNP. This combined strengthening mechanism can be well presented by evolution of atomic configurations.